State of coenopopulations of wild berry plants in the territory of Kazakhstan Altai - Vdovina, T.A.; Lagus, O.A.; Isakova, E.A.; Vinokurov, A.A. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2024)
In the article studies on the state of the coenopopulations: Rosa acicularis Lindl., Rosa spinosissima L., Lonicera altaica Pall., Ribes nigrum L., Ribes petraeum Wulfen, which have high resource indicators and significant areas were presented. The studies were conducted on the territory of the Kazakhstan Altai in the geographical areas of South-West Altai, South Altai. For each coenopopulation, data were obtained on the nature of distribution, occupied area, phytocenotic characteristics, general and age condition of plants and their biodiversity.
Қазақстандық Алтай аумағындағы жабайы жеміс өсімдіктерінің ценопопуляцияларының жай-күйі
Состояние ценопопуляций диких плодовых растений на территории Казахстанского Алтая
Keywords: coenopopulation; phytocenosis; area; productivity; variation